Microstrip Leaky-Wave Antenna with Circular Polarization and Broadside Radiation - Ahmad, Ayaz; Mukherjee, Jayanta (IEEE antennas and wireless propagation letters, 2023)
In this letter, a novel circularly polarized microstrip leaky-wave antenna is proposed with broadside radiation and high gain. A conventional microstrip patch has been modified to obtain broadside gain along with circular polarization. The modified patch is periodically placed along one side of the 50 Ω delay line to form leaky-wave antenna. The optimized broadside frequency of the antenna is 10.1 GHz. The bandwidth associated with 3-dB axial ratio is 13.3% while the maximum obtained gain is 15.8 dBic. The measured gain variation within 3-dB axial ratio bandwidth is 1.6 dB. Measured results of the fabricated antenna follow the simulations.